Contemporary Collaborative Consumption Trust and Reciprocity Revisited (Kritische Verbraucherforschung,, 2018)
This book provides critical perspectives on contemporary collaborative consumption, a recent societal phenomenon shaking up previously fixed socio-economic categories such as the producer and the consumer. The contributors discuss the role of trust and reciprocity in collaborative consumption through seven case studies. The chapters advance debates on the contradictions of positioning collaborative consumption as possible solutions for a more sustainable development and exacerbating new forms of inequalities and injustice. The book contributes a nuanced appraisal of social and economic activity for reflecting socio-technological changes in contemporary societies. Content Reciprocity in the sharing economy: the case for time banking platforms • Collective representation on collaborative economy platforms • "Foodsharing": Reflecting on individualized collective action in a collaborative consumption community organization • Riding free-riders? A study of the phenomenon of BlaBlaCar in Italy • The sharing economy and young people: an exploratory research project • Collaborative consumption and trust-building processes in the emerging new food economy • Shared use and owning of clothes: borrow, steal or inherit The Editors Isabel Cruz, Institute of Sociology at the Faculty of Letters at the University of Porto. Rafaela Ganga, Research Associate at the Institute of Cultural Capital (ICC) at the University of Liverpool and Liverpool John Moores University. Stefan Wahlen, Assistant Professor for "Consumption Governance" at the Sociology of Consumption and Households group at Wageningen University. .